Sudden extensive bloody pleural and pericardial effusion in a subject with untreated known hypothyroidism after total thyroidectomy, triggered by pneumonia - Iwamoto, Yuichiro; Tatsumi, Fuminori; Katakura, Yukino; Dan, Kazunori; Wamata, Ryo; Kimura, Tomohiko; Shimoda, Masashi; Nakanishi, Shuhei; Kaku, Kohei; Mune, Tomoatsu; Kaneto, Hideaki (BMC endocrine disorders, 2022)
Background In subjects with hypothyroidism, edema is often observed, and pleural effusion and pericardial fluid could be also observed. The color of such fluid retention is usually yellow. Here we show a very rare case with hypothyroidism who had bloody pleural effusion and bloody pericardial fluid. Case presentation A 42-year-old male noticed chest pain and the aggravation of exertional dyspnea, and he was transported to our institution by emergency. He had Graves' disease and underwent total thyroidectomy about 4 years before. After then, he had been treated with 200 [mu]g/day of levothyroxine sodium for the maintenance of thyroid function. However, he self-interrupted such medication about 2 years before. Thyroid function on admission was reduced as follows: free triiodothyronine, 1.60 pg/mL; free thyroxine < 0.40 ng/dL; thyroid-stimulating hormone 25.50 [mu]U/mL. Inflammation markers were increased: white blood cells 25,280 /[mu]L; C-reactive protein 18.66 mg/dL. A large amount of pericardial fluid and pleural effusion were observed in chest and abdominal computer tomography and echocardiography. In addition, we performed pleural effusion and pericardial fluid collection. Pleural effusion in this subject showed bloody color, but not yellow. In cell block specimen of pleural effusion and pericardial fluid, red blood cells, neutrophils and lymphocyte component were observed. In this subject, however, we were unable to find any obvious background disease causing bloody pericardial effusion. Finally, we concluded that bloody pleural effusion and bloody pericardial fluid were brought about in a subject with untreated known hypothyroidism after total thyroidectomy, triggered by pneumonia. Conclusions In subjects with hypothyroidism, fluid and mucopolysaccharide are stored in interstitial space and protein osmolality is increased, thus leading to edema and fluid retention. It is noted here that pleural effusion and pericardial fluid in this subject showed bloody color and included red blood cells. There are no reports of bloody pericardial fluid with hypothyroidism. Therefore, it is important to keep in mind that a subject with some trigger, such as infection, may have a hematologic fluid retention that is not seen when hypothyroidism is present alone, as observed in this subject. Keywords: Hypothyroidism, Bloody pleural effusion, Bloody pericardial fluid, Case report